Rake-receivers in the modern telecommunication systems (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2007)
The evolution of the systems is considered with the code division. It is investigational principles of construction and work of Rake-receiver, and also changes which bring in the new standards of connection in a receiver.